Cytochemistry of fat body trophocytes and ovaries of workers and queens of Melipona quadrifasciata anthidioides (Hymenoptera: Apidae: Meliponini) during vitellogenesis - Paes-De-Oliveira, Vagner Tadeu [UNESP]; Roat, Thaisa Cristina [UNESP]; Berger, Bruno [UNESP]; Da Cruz-Landim, Carminda [UNESP] (Wiley-Blackwell, 2012)
The fat body (FB) of insects is where yolk proteins are synthesized. Therefore, relationships between the FB and oogenesis were studied in nurse workers, virgins, and physogastric queens of Melipona quadrifasciata anthidioides, a stingless bee in which the workers produce and lay eggs while provisioning brood cells. The relationships between FB and oogenesis, as well as the routes of materials from hemolymph to the oocytes, were studied through the cytochemical detection of lipids by osmium imidazole (OI), carbohydrates by ruthenium red (RR) and basic proteins by ammoniacal silver (AS). The results show differences in the presence of the studied materials in FB trophocytes and ovary of the classes of females studied and oogenesis phases. Material that tested positive for the treatments was detected among the classes of individuals studied in both, trophocytes and oocytes, and in the route of those materials from hemolymph to the oocytes. The differences found among the individual classes indicate relationships with the nutrition and adaptation to the parsimonious use of nutrients in the metabolism of reproduction. Microsc. Res. Tech., 2012. (C) 2012 Wiley Periodicals, Inc.
Keywords: oogenesis; stingless bee; nurse workers; virgins queens; physogastric queens